Social Conflicts in the Portuguese Revolution, 1974–1975 - Varela, Raquel; Alcântara, Joana (Labour / Le Travail, 2014)
The Portuguese Revolution, the process popularly known as the “Carnation Revolution” that lasted from 25 April 1974 to 25 November 1975, took place against a backdrop of military humiliation in defeat by peasant guerilla movements in the Portuguese colonies of Guinea-Bissau, Angola and Mozambique. However, an analysis of four distinct types of social conflicts – strikes; demonstrations; occupations of factories, other workplaces, and public services; and occupations of vacant houses – suggests that class struggle within Portugal was the essential dynamic of the Revolution. Revolution came to Portugal through an active workers’ movement against fascism within the context of a global economic crisis. Working people had decided it was time for democratic change.